Examination of export and production performances of textile companies making export-focused production on the return to normal life from pandemic - Cakir, Fatma Sonmez; Adiguzel, Zafer; Zehir, Songul Yesilot; Zehir, Cemal (EMERALD GROUP PUBLISHING LTD, 2024)
Purpose The purpose of this study is to examine the effects of production capabilities, competition intensity and marketing and sales capabilities on the export and production performances of textile companies engaged in export-oriented production return to normal life from the pandemic. Design/methodology/approach Within the scope of the research, a sample of 683 white-collar expert participants was taken and a scale consisting of 29 statements in total was presented to them. The structural equation modeling (SEM) model was analyzed with the study SmartPLS. At the first stage, the relations between the scale expressions and the variables were given with factor loads and weights, validity/reliability analyzes were made for the model, and finally, the research model was tested. Findings As a result of the analysis in the research, it can be explained that the production capabilities and marketing and sales capabilities are important for the performance of the companies, at the same time the intensity of competition keeps the companies in a dynamic structure and the intensity of competition is also important for the companies to develop themselves. Research limitations/implications Considering the limitations of the research, data were collected from white-collar employees working in export-oriented textile companies in Istanbul. Because in order to answer the questions about the variables representing the research model, expert and authorized employees were required. Practical implications It can be explained that the performance of companies in the production sector is positively affected if they discover opportunities in risky environments so that they can gain an advantageous position over their competitors in an intense competitive environment. Because it can be assumed as a result of the analysis that textile companies want to evaluate the opportunities in the competitive environment by using their production, marketing and sales abilities during the pandemic process. Originality/value The research is unique in that it sets an example for future studies by examining the effects of production capabilities, competitive intensity and marketing and sales capabilities, which are likely to affect the performance of textile companies in the return of normal life from pandemic conditions.
Keywords: Production capabilities; Competitive intensity; Export performance; Marketing; Sales capabilities; Production performance; VENTURE PERFORMANCE; FIRM PERFORMANCE; INNOVATION; ORIENTATION; CAPABILITIES; MEDIATION; STRATEGY; MARKET; SALES; Computer Science